Rethinking abusive supervision: antecedents and reparative mechanisms of abusive supervision, including supervisor frustration, coworker support, guilt, and supervisor OCB in a mediated-moderation model - Kashif, Muhammad; Naheed, Rehana; Wijenayake, Shanika (Review of Business Management, 2023)
Purpose – Drawing on affective events theory, this study positions role overload and supervisor frustration as antecedents of abusive supervision, leading to supervisor-led organizational citizenship behavior. In a mediated-moderationsed analysis, we question whether coworker support moderates the relationship between supervisor frustration and abusive supervision and whether guilt mediates between abusive supervision and supervisor-led OCB. Theoretical framework– This research study is inspired by the assumptions of affective events theory. Design/methodology/approach – In a time-lagged survey, we collected data from 351 medical supervisors employed in private hospitals in Pakistan. The PROCESS macro is used to perform a mediated-moderation analysis. Furthermore, the research is analyzed based on structural equation modeling (SEM) proceduresusing the AMOS software, version 26.0. Findings – The results demonstrate hat role overload predicts supervisor frustration, leading to abusive supervision. Moreover, when coworker support is high, the relationship between supervisor frustration and abusive supervision is weaker. Supervisor frustration and guilt mediate the path from role overload to supervisor frustration, abusive supervision,and supervisor OCB, respectively. Practical & social implications of research– Organizational policymakers should consider role overload as an element that causes stress and frustration among medical supervisors, resulting in abusive behavior towards their subordinates. Thus, some normative measures might be appropriate to reduce abusive supervision in the healthcare sector. Socially, this study can help in combating frustration and aggression among working people,representing a significant proportion of Pakistani society. Originality/value – The mediators, such as supervisor frustration and guilt, advance our understanding of abusive supervision research. Keywords: Abusive supervision, supervisor OCB, guilt, affective events theory, coworker support.